Optimal Control Problem for a Modified Novikov Equation with Dissipation - , Jiangbo Zhou, Jing Chen, Junde Chen (Archives of Current Research International, 2015)
This paper investigate the optimal control problem for a modified Novikov equation with dissipation. The existence and uniqueness of regular local solution to the corresponding initial boundary value problem is guaranteed by the Faedo-Galerkin method. A critical estimate of the solution is obtained. Finally, the existence of an optimal solution to the control problem is proved.